Grief care to children ophaned by HIV and AIDS within Nairobi province Kenya : towards a pastoral strategy for identity formation - Nguru, Janet (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.